Utilization of Volleyball Teaching Materials Based on Augmented Reality - Asep Suharta; Nurkadri; Rahma Dewi; Bessy Sitorus Pane; Muhammad Reza Destya (LPPM Undiksha, 2024)
Many teachers need more ability to use and operate educational technology, especially ICT-based. So, there is a need for innovation in developing teaching materials, especially those based on AR, to improve the quality of learning, student interest and motivation, and understanding of the concepts taught. This research aims to develop teaching materials for volleyball based on augmented reality. The resulting product is augmented reality-based volleyball teaching materials that can be used for PJOK students and teachers. The type of research used in this study is Research and Development (R&D) using the ADDIE research model. This study uses subjects consisting of 30 students, one material expert, one media expert, and one practitioner. The data collection method used was a questionnaire using an instrument as a questionnaire sheet. After the data was collected, it was analyzed using quantitative and qualitative methods. The results of the small group test concluded that the development of teaching materials for augmented reality-based volleyball materials had met the criteria to continue in the small group test because the percentage of teaching materials for augmented reality-based volleyball materials was 80%, and teaching materials for augmented reality-based volleyball materials after an extensive group test of 95%. It can be concluded that augmented reality-based volleyball teaching materials can assess students' abilities. This research is expected to add insight into students' playing volleyball.